Data from: Variation in age and size in Fennoscandian three-spined sticklebacks (Gasterosteus aculeatus) - DeFaveri, Jacquelin; Merilä, Juha (2013)
Average age and maximum life span of breeding adult three-spined sticklebacks (Gasterosteus aculeatus) were determined in eight Fennoscandian localities with the aid of skeletochronology. The average age varied from 1.8 to 3.6 years, and maximum life span from three to six years depending on the locality. On average, fish from marine populations were significantly older than those from freshwater populations, but variation within habitat types was large. We also found significant differences in mean body size among different habitat types and populations, but only the population differences remained significant after accounting for variation due to age effects. These results show that generation length and longevity in three-spined sticklebacks can vary significantly from one locality to another, and that population differences in mean body size cannot be explained as a simple consequence of differences in population age structure. We also describe a nanistic population from northern Finland exhibiting long life spans and small body size.